The high affinity IgE receptor: a signaling update. (October 2021) - Blank, Ulrich; Huang, Hua; Kawakami, Toshiaki
Highlights: Differences in affinity, valency, concentration of FcεRI-aggregating ligands are translated into distinct signaling outcomes. Mast cell degranulation implicates a highly complex molecular machinery regulating granule transport and membrane fusion. Advances made in signaling-dependent cytokine and chemokine gene transcription in response to antigenic stimulation. Abstract : Here we update receptor proximal and distant signaling events of the mast cell high affinity IgE receptor (FcεRI) launching immediate type I hypersensitivity and an inflammatory cytokine-chemokine cascade. Different physiologic antigen concentrations, their affinity, and valency for the IgE ligand produce distinct intracellular signaling events with different outcomes. Investigating mast cell degranulation has revealed a complex molecular machinery that relays proximal signaling to cytoskeletal reorganization, granule transport and membrane fusion. Several new phosphorylation- and calcium-responsive effectors have been described. FcεRI signaling also promotes de novo gene transcription. Recent progress has identified enhancers at genes that are upregulated in mast cells after stimulation through FcεRI using next generation sequencing methods. Enhancers at genes that respond to antigenic stimulation in human mast cells revealed Ca 2+ -dependency. Stimulation-responsive super enhancers in mouse mast cells have also been identified. Mast cell lineage-determining transcription factor GATA2 primes these enhancers to respond to antigenic stimulation.